Organomercury oligonucleotide-polydopamine nanoparticle assemblies discriminate between target sequences by Hg(ii)-mediated base pairing - Kotammagari, Tharun K.; Al-Waeel, Majid; Lukkari, Jukka; Lönnberg, Tuomas (Royal Society of Chemistry, 2025)
A fluorescently tagged oligonucleotide hybridization probe incorporating a single 5-mercuricytosine residue was synthesized and found to adsorb on polydopamine nanoparticles much more strongly than its unmetallated counterpart. Hybridization with target sequences led to release of the probe from the nanoparticle to varying degrees depending on the nucleobase opposite to 5-mercuricytosine.